Pengaruh Membangun Budaya Organisasi dalam Meningkatkan Produktivitas untuk Memenuhi Kepuasan Pelanggan CV Family Group Kerupuk Jangek - Zahra Nadhira Islamy; Titin Wardaini; Syukri Ramadhan; Adiprana Mahendra; Adrianto Nurul Rizky; Vivi Nila Sari (BADAN PENERBIT STIEPARI PRESS, 2024)
This community service aims to determine the effect of building organizational culture in increasing productivity to meet CV Family Group customer satisfaction. Organizational culture has an influence on increasing the productivity produced by employees. Good productivity greatly determines customer satisfaction. The problems found when conducting research were: uncertain supply of raw materials, less strategic location, and many competitors who have similar businesses. The solution to this problem is to look for other suppliers so that there is no shortage of raw materials, the products produced must always be of good quality and taste good so that customers are satisfied and the business is able to compete in market share. This article was prepared by observation, collecting data in interviews, and documentation. The results of this research show that customer satisfaction depends on the products produced and the services provided by employees.